Water power newsletter launched - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
HYDRONET Water power newsletter HYDRONET- FAKT - Gansheidestrasse 43 - D-7000 Stuttgart- 1 GERMANY